Behavior of non-Transmissible Chronic Diseases in Elder Adults - Raidel González Rodríguez; Juan Cardentey García (Revista Finlay)
Foundation: non transmissible chronic diseases are the main causes of morbi-mortality mainly in elder adults. Objective: to characterize the behavior of non-transmissible chronic diseases in elder adults of the medical office no 2 during 2016. Methods: a cross descriptive retrospective study was done at the medical office no2 belonging to the Pedro Borrás Astorga polyclinic at Pinar del Río during 2016. The universe of study was 348 elder adults with the diagnosis of non-transmissible chronic disease. The variables used were age, sex, non-transmissible chronic disease, number of chronic diseases. The results were expressed in absolute or relative frequencies by means of statistic tables and graphs. Results: in the research the female sex, the age group of more than 75 years old and more predominated so as arterial hypertension as the chronic disease suffered by the elder adults of both sexes. The age groups of 60 to 64 and 65 to 69 mostly presented 1 non transmissible chronic disease. The group of 70 to 74 showed 2 while the group of 75 or more had 3. The familial antecedent of first degree prevailed and the smoking habit as risk factor. Conclusion: non transmissible chronic diseases are a health problem for elder adults of the medical office no2. In the study women older than 75 years prevailed so as hypertension in both sexes. With aging the presence of more than 1 co morbidity, familial antecedent was the higher so as the smoking habit.